THE USE OF PICTURE AND PICTURE TECHNIQUE IN IMPROVING STUDENT WRITING SKILL - Nurhajah Tia Sarifah; Yanuarti Apsari (IKIP Siliwangi, 2020)
This study is aimed to know whether picture and picture technique can improve students’ writing skill. The method used was quantitative research with one group pre-test and post-test research design. The population was the 11th grade students at SMK Tunas Bangsa. The sample was one class of mechanical engineering major and consisted of 35 students.The result showed that null hypothesis of this study was rejected. It is proved by the data from T-test that shows the Sig. 2 tailed is 0.000. This value is less than 0.05. Null hypothesis, therefore, was rejected. This means that picture and picture could improve students’ writing skill. Keywords: Picture And Picture, Writing, Descriptive Text